Sexual Exploitation in Child Trafficking (Case Study Decision Number 29/Pid.Sus/2019/PN.Tim and 311/Pid.Sus/2021/PN.Pol) - Kurnianingsih, Marisa; Saputri, Irwinda Mutiara; Hartanto; Iksan, Muchamad (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of writing this article is to explain the judge's considerations in deciding the practice of sexual exploitation in the crime of child trafficking based on court decision number 29/Pid.sus/2019/PN.Tim and Decision Number 311/Pid.sus/ 2021/PN.Pol. This decision provides a clear picture of the continued practice of trafficking children for sexual exploitation in Indonesia. The practice of trafficking children for sexual exploitation occurs because the victims are still minors so their minds are not yet perfect in making decisions and following up on what they have experienced. This is what exploiters take advantage of. The facts revealed at trial are of course the basis for judges in examining and deciding exploitation cases. Writing this article uses a normative juridical approach with a descriptive type where the author will explain the legal basis relating to sexual exploitation and the judge's considerations in Decision Number 29/Pid.Sus/2019/PN. Team and Decision Number 311/Pid.Sus/2021/PN. Pol. In the results and discussion, it is known that the government has issued several regulations that can be used to provide repressive legal protection for children, including Law Number 35 of 2014 concerning Child Protection. Decision Number 29/Pid.Sus/2019/PN. Team and Decision Number 311/Pid.Sus/2021/PN. The police also use the Child Protection Law to examine and decide cases of sexual exploitation in child trafficking